SAT0301 THE USE OF 16 GRIPS TEST TO EVALUATE HAND IMPAIRMENT IN SYSTEMIC SCLEROSIS (SSC): PRELIMINARY TO CONSTRUCTION OF PERSONALIZED DEVICES. (June 2019) - Tonelli, Roberto; Anastasio, Chiara; Schiavi, Margherita; Lucia, Zingarello; Giuggioli, Dilia; Mascia, Maria Teresa
Abstract : Background: Systemic sclerosis (SSc) is a progressive connective tissue disease of unknown etiology characterized by autoimmune response and changes in the microvascular system. Although skin fibrosis represents the primary element of this disease, patients may present muscular and/or joint damage. Hand impairment is a major cause of morbidity and disability in about 90% of SSc patients. The ADL difficulties are similar to those of patients with rheumatoid arthritis but SSc patients use a low number of assistive device. In our center an interdisciplinary research unit composed of rheumatologists, rehabilitators, occupational therapists, and design engineers, with the directly involvement of the SSc patients within the design team, are developing a design method to prototype ergonomic assistive device personalized for hands. Objectives: Evaluate through the 16 grip test which were the most difficult grips for SSc patients in order to understand what particular changes we need to focus on more rehabilitative attention. Determine what ADL can be linked to difficult grips to understand how to work on it. Give advice and design appropriate customized ergonomic aids. Methods: 92 patients (79 females and 13 males) with SSc followed by our tertiary Universitary based Rheumatologic Center have been specifically evaluated by Hand Rehabilitation Service. The average age of patients was 56y. The 16 grip test was used to evaluate patients. It includes 16 different pattern of grip divided into power grip and precision pinch - Moreover it tests basically two different grip and pinch modalities: static prehension and dynamic prehension. The score for each grip goes from 0 to 4 (0=impossible, 1=realized with high difficulty, 2=medium difficulty, 3= low difficulty, 4=normal). Results: 30 patients (32%) had no grip problem, 9 only on the left and 5 on the right hand; 4 patients presented grip difficulty in both hands with a reduction> 25%. 31 had difficulty in 2 or more grip pattern. The most interested grips are the monodigital and pluridigital pressure, the tip to tip pinch, the extension grip in both sexes; the teno-digital in males and the digito-palmar in females. Over 60% of the grips were normal; in particular in our patients only few deficiencies in the power and in the static prehension grips were reported. The most interested patterns of grips are in the group of precision handling related to the use of the pads; the extension grip to the difficulty in opening the first commissure. Conclusion: Over 60% of the grips were normal.; in particular in our patients only few deficiencies in the power grips and in the static prehension grips were reported. The most interested patterns of grips are in the group of precision handling related to the use of the fingertips; the extension grip to the difficulty in opening the first commissure. The problems of hand impairment are restricted to a subset of patients around 10-15%. From these results we can obtain useful data to construct our personalized devices for SSc hands. References: [1] A Co-Design Method for the Additive Manufacturing of Customised Assistive Devices for Hand Pathologies. F Gherardini, MT Mascia, V Bettelli, F Leali. JIDPS Pre-press, pp. 1-18, 2018 Disclosure of Interests: None declared